2017
DOI: 10.1111/ene.13397
|View full text |Cite
|
Sign up to set email alerts
|

Progression of prodromal motor and non‐motor symptoms in the premotor phase study – 2‐year follow‐up data

Abstract: Our study shows that the frequency of non-motor prodromal markers is higher in the HR-PD group but does not increase within 2 years. The progression of motor and non-motor markers seems to be independent, but higher baseline non-motor burden is associated with the motor status after 2 years. Moreover, our data argue for a high impact of motor markers in the risk estimation for future PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Our study strengthens the notion of NMS antedating motor symptoms in PD by assessing the presence and time of onset of the full spectrum of pNMS using a validated NMS questionnaire (NMSQuest) in a population with recently diagnosed PD. Interpretation of previous studies evaluating the frequency and duration of onset of pNMS is limited by study methodological variability, lack of direct patient evaluation , long duration from PD diagnosis to study enrolment , utilization of non‐validated, custom‐made NMS questionnaires or studying only limited subsets of the spectrum on pNMS in PD cohorts or ‘at risk’ of PD cohorts .…”
Section: Discussionmentioning
confidence: 99%
“…Our study strengthens the notion of NMS antedating motor symptoms in PD by assessing the presence and time of onset of the full spectrum of pNMS using a validated NMS questionnaire (NMSQuest) in a population with recently diagnosed PD. Interpretation of previous studies evaluating the frequency and duration of onset of pNMS is limited by study methodological variability, lack of direct patient evaluation , long duration from PD diagnosis to study enrolment , utilization of non‐validated, custom‐made NMS questionnaires or studying only limited subsets of the spectrum on pNMS in PD cohorts or ‘at risk’ of PD cohorts .…”
Section: Discussionmentioning
confidence: 99%
“…This result indirectly implies the slow evolution of NMSs. A study on progression markers in the premotor phase of PD showed that the frequency of nonmotor prodromal markers did not increase within 2 years, and that the progression of motor and nonmotor markers seemed independent 7 . Erro et al conducted a 2-year prospective clinical study of NMSs in patients with PD in Naples, Italy 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Dysarthria in Parkinson's disease (PD), which is a progressive neurodegenerative disease characterized by progressive loss of dopaminergic neurons in the substantia nigra, is universal [1][2][3][4][5][6][7][8]. It was indicated that almost 89% of patients with PD developed dysarthria [9][10][11].…”
Section: Introductionmentioning
confidence: 99%